2021
DOI: 10.3390/ijerph18126263
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Second-Hand Smoke in Public Places and Barriers to the Implementation of Smoke-Free Regulations in The Gambia: A Population-Based Survey

Abstract: Introduction: Second-hand smoke is associated with more than 1.2 million deaths per year among non-smokers. Smoking in public places is prohibited in The Gambia but there is no information on the level of exposure to second-hand smoke among adolescents and adults 15–64 years. The aim of this study was to assess the level and predictors of exposure to second-hand smoke in public places and compliance with smoke-free regulations in The Gambia. Methods: A population-based survey was conducted in an established He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Findings suggest that the positive attitude of venue owners and staff toward the smoke-free policy serves as a facilitator. This is consistent with existing literature, which has shown that public awareness and support for smoke-free legislation contributed to effective smoke-free policy implementation 13 , and increased support is associated with knowledge of the harmful effects of SHS 14 , 15 and the requirements of the smoke-free legislation 16 , 17 . Strengthening public knowledge about the adverse effects of SHS and the health benefits of the smoke-free policy can help hospitality venue owners and staff to better enforce the smoking ban.…”
Section: Discussionsupporting
confidence: 91%
“…Findings suggest that the positive attitude of venue owners and staff toward the smoke-free policy serves as a facilitator. This is consistent with existing literature, which has shown that public awareness and support for smoke-free legislation contributed to effective smoke-free policy implementation 13 , and increased support is associated with knowledge of the harmful effects of SHS 14 , 15 and the requirements of the smoke-free legislation 16 , 17 . Strengthening public knowledge about the adverse effects of SHS and the health benefits of the smoke-free policy can help hospitality venue owners and staff to better enforce the smoking ban.…”
Section: Discussionsupporting
confidence: 91%
“…A recent analysis of SHS exposure among adolescents aged 12–15 years across 68 LMICs also reported a positive association between SHS exposure and parental smoking, with the association being larger for maternal smoking than paternal smoking [ 28 ]. Another study in The Gambia also found that lower education attainment, lower household income, urban residence, and not being aware of smoke-free regulations increased the risk of SHS exposure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The country ratified the WHO Framework Convention on Tobacco Control in September 2007 22. There are several regulations and policies on tobacco control in The Gambia, including the Prohibition of Smoking in Public Places Act 1998, the Tax Policy Reform Act 2013, the Tobacco Control Act 2016 and the Tobacco Control Regulations 2019 23 24. These legal instruments seek to protect children from exposure to tobacco products.…”
Section: Introductionmentioning
confidence: 99%
“…These legal instruments seek to protect children from exposure to tobacco products. However, despite the numerous achievements in tobacco control as highlighted above, there are still gaps, especially on the implementation of smoke-free regulation in the Gambia 24. There has also been some regression, specifically with the Tax Policy Reform Act, which has been stalled since 2017, following a change in government.…”
Section: Introductionmentioning
confidence: 99%